2022
DOI: 10.1002/anie.202213190
|View full text |Cite
|
Sign up to set email alerts
|

Superior Metal‐Organic Framework Activation with Dimethyl Ether

Abstract: Metal-organic frameworks (MOFs) are demonstrated to be readily activated by treatment with the low surface tension, low boiling point solvent dimethyl ether (DME). The mildness of the method enables access to high surface areas by avoiding structural changes in the framework that often plague thermal activation methods. A distinction from previous methods is that DME activation succeeds for materials with coordinatively unsaturated sites (CUS) and non-CUS MOFs as well. DME displaces solvent molecules occupying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Matzger and co-workers have additionally developed protocols for the gentle activation of MOFs with dimethyl ether (DME), even demonstrating thorough activation of coordinatively unsaturated MOFs such as HKUST-1 at temperatures 50−80 °C less than routine activation practices. 180 Indeed, this relatively low temperature activation protocol provides another handle toward activating metastable materials, including noncovalent frameworks.…”
Section: Activation Of Noncovalent Organic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Matzger and co-workers have additionally developed protocols for the gentle activation of MOFs with dimethyl ether (DME), even demonstrating thorough activation of coordinatively unsaturated MOFs such as HKUST-1 at temperatures 50−80 °C less than routine activation practices. 180 Indeed, this relatively low temperature activation protocol provides another handle toward activating metastable materials, including noncovalent frameworks.…”
Section: Activation Of Noncovalent Organic Frameworkmentioning
confidence: 99%
“…With careful shifting of temperature–pressure conditions, the supercritical fluid is transitioned into the gas phase, ultimately leading to an appreciably gentle gas-like activation mechanism with negligible capillary forces in which any miscible solvent is simultaneously removed. Matzger and co-workers have additionally developed protocols for the gentle activation of MOFs with dimethyl ether (DME), even demonstrating thorough activation of coordinatively unsaturated MOFs such as HKUST-1 at temperatures 50–80 °C less than routine activation practices . Indeed, this relatively low temperature activation protocol provides another handle toward activating metastable materials, including noncovalent frameworks.…”
Section: Activation Of Noncovalent Organic Frameworkmentioning
confidence: 99%
“…It has been widely observed for MOFs, COFs, and 2DPs that attempting to isolate high boiling points directly by thermal activation of the reaction solvent is unsuccessful. Farha, Matzger, and coworkers reported a strategy to address this in MOF crystallites by exchanging high boiling solvents for low boiling solvents prior to vacuum drying at elevated temperatures 46,54 . Using this strategy for different classes of MOFs, they found that the crystallinity, high surface area, and narrow pore size distribution could be retained when using this solvent exchange strategy.…”
Section: Thermal Activationmentioning
confidence: 99%
“…In particular, MOFs with coordinatively unsaturated sites (CUS) are especially difficult to fully activate due to the strong interaction of solvent with the metal centers. 20 Nonetheless, when these strong affinity sites are accessible, the CUS is advantageously employed for selective gas adsorption, 21,22 separations, 23,24 catalysis, 25,26 and in sensing applications. 27,28 In addition, the CUS provides potential sites for expanding the chemical functionality of MOFs through grafting.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While much progress has been made to improve activation methods of porous materials using ultralow surface tension exchange solvents and supercritical CO 2 , , the reproducible preparation of high surface area materials remains non-trivial. In particular, MOFs with coordinatively unsaturated sites (CUS) are especially difficult to fully activate due to the strong interaction of solvent with the metal centers . Nonetheless, when these strong affinity sites are accessible, the CUS is advantageously employed for selective gas adsorption, , separations, , catalysis, , and in sensing applications. , In addition, the CUS provides potential sites for expanding the chemical functionality of MOFs through grafting. ,, Therefore, efforts to improve the surface area of CUS-MOFs are critical for achieving their full functionality.…”
Section: Introductionmentioning
confidence: 99%